Head Injury In An Apple Picker - Gregory Stephen Kohls; Raymond Ten Eyck (Association of American Medical Colleges, 2011)
Abstract This simulation case was developed to provide residents with an immersive clinical experience that simulates the diagnostic and treatment challenges incorporated in the emergency department care of an anticoagulated patient presenting with a traumatic brain injury. The case involves a closed head injury in an elderly patient on warfarin. The patient initially presents with a GCS of 15. He subsequently deteriorates neurologically. CT of the head shows a subdural hemorrhage with midline shift. The case focuses on appropriate reversal of anticoagulant therapy, airway management, and treatment of a patient with elevated intracranial pressure. While this case has not been fully integrated into the residency curriculum at our institution, it has been run several times with current residents. They found the case to be challenging, educational, and an effective learning tool for the treatment of an anticoagulated patient with a traumatic brain injury. This simulation case was also incorporated into a training program for the development of a trauma program in a local community hospital. Nurses and technicians served as the learners. The case allowed for the development of teamwork in a critical trauma scenario. One hundred and thirty-eight learners experienced the case. All ratings from these learners were in the good to excellent category.